From Service Quality to Loyalty: Understanding Rail Commuter Satisfaction in Greater Kuala Lumpur - Kalhoro, Maryam; Au Yong, Hui Nee; SPR, Charles Ramendran (Transportation Development Research, 2025)
Rapid urbanization in Greater Kuala Lumpur has intensified automobile dependency, causing congestion and environmental concerns. Although urban rail systems are promoted as sustainable alternatives, their adoption remains limited. This study examines how service quality influences commuter loyalty and whether satisfaction mediates this relationship within Malaysia’s urban rail context (KTM Komuter, LRT, MRT). A structured questionnaire yielded 218 valid responses analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that service quality does not directly predict behavioural intention (β = 0.07, t = 0.874, p > 0.05). Instead, commuter satisfaction significantly predicts behavioural intention (β = 0.728, t = 10.338, p < 0.001) and fully mediates the link between service quality and behavioural intention (β = 0.515, t = 8.53, p < 0.001). Enhancing commuter satisfaction is therefore essential to increase rail usage, as improvements in service quality influence behaviour only when they raise satisfaction. Theoretically, the findings integrate the SERVQUAL model with the Theory of Planned Behaviour (TPB); practically, they guide policymakers in strengthening rail services to promote sustainable urban mobility.